(X-4)(x+12)=

Simple and best practice solution for (X-4)(x+12)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X-4)(x+12)= equation:


Simplifying
(X + -4)(x + 12) = 0

Reorder the terms:
(-4 + X)(x + 12) = 0

Reorder the terms:
(-4 + X)(12 + x) = 0

Multiply (-4 + X) * (12 + x)
(-4(12 + x) + X(12 + x)) = 0
((12 * -4 + x * -4) + X(12 + x)) = 0
((-48 + -4x) + X(12 + x)) = 0
(-48 + -4x + (12 * X + x * X)) = 0
(-48 + -4x + (12X + xX)) = 0

Reorder the terms:
(-48 + 12X + -4x + xX) = 0
(-48 + 12X + -4x + xX) = 0

Solving
-48 + 12X + -4x + xX = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 12X + -4x + 48 + xX = 0 + 48

Reorder the terms:
-48 + 48 + 12X + -4x + xX = 0 + 48

Combine like terms: -48 + 48 = 0
0 + 12X + -4x + xX = 0 + 48
12X + -4x + xX = 0 + 48

Combine like terms: 0 + 48 = 48
12X + -4x + xX = 48

Add '4x' to each side of the equation.
12X + -4x + 4x + xX = 48 + 4x

Combine like terms: -4x + 4x = 0
12X + 0 + xX = 48 + 4x
12X + xX = 48 + 4x

Reorder the terms:
-48 + 12X + -4x + xX = 48 + 4x + -48 + -4x

Reorder the terms:
-48 + 12X + -4x + xX = 48 + -48 + 4x + -4x

Combine like terms: 48 + -48 = 0
-48 + 12X + -4x + xX = 0 + 4x + -4x
-48 + 12X + -4x + xX = 4x + -4x

Combine like terms: 4x + -4x = 0
-48 + 12X + -4x + xX = 0

The solution to this equation could not be determined.

See similar equations:

| 2x-21=x+4 | | x^2+17=19 | | 40x-18(x-3)=468 | | y+6.2=9.1 | | 63=c-21+2c | | 3/6=/8 | | 16+x=42 | | 3.29-0.223= | | 4t^2-20t-60=0 | | 2sin(30+x)=3cosx | | 2+p=2 | | 5n-6=7 | | ln(x)+ln(1.1675x)=5.28 | | 5x-6=93-6x | | 5t+4=11 | | -14=x/2 | | (3x-9)(2x-2)= | | 4.500+60v=50(100+v) | | 4(13-y)+2y=36 | | -42+14x=4y | | 3y+2x-7+12-6x+4y=56-45x+2y | | (c+2)=5(c+1)-7 | | n-3=1 | | -5v=-5 | | 32+(-16)+(-12)= | | 2(c+2)=5(x+1)-7 | | -3x^4+5x^3-2x^2+9=0 | | y=3x^5-4x^2+2 | | 3/5n=6 | | 3y-8+6x= | | (3x^2-2x+4)-(-5x^2+3x-8)= | | 11v-12/v-5 |

Equations solver categories